Implementasi Aplikasi Analisis Beban Kerja Terkait Kinerja Pegawai di Dinas Pendidikan Kota Surabaya - Zacky Aqshal Dhamara Putra; Hasan Ismail (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
The implementation of Minister of State Apparatus Empowerment and Bureaucratic Reform Regulation Number 1 of 2020 regarding Guidelines for Job Analysis and Workload Analysis has been carried out. In Indonesia, workload analysis is important for determining the number of employees needed by the Surabaya Education Office so that the organizational structure can be efficient in carrying out its tasks. This study aims to evaluate the implementation of the Workload Analysis Application (ABK) on employee performance at the Surabaya Education Office. The research method used is descriptive qualitative using documentation, observation, and interviews. The ABK application is used to determine the needs of employees at the Surabaya Education Office. Data were collected through documentation, observation, and interviews. The results show that the procedure for using the Workload Analysis Application is in accordance with the guidelines set forth in the Ministerial Regulation. Human resources and infrastructure are quite good because socialization has been conducted to employees. Although the implementation is going well, there are still obstacles related to understanding the ABK filling format by some human resources and the need for additional computer facilities and improvements to an unstable network.